Governance and Youth Development: Experiences of the Village Development and Security Committees (Journal of Governance and Development (JGD), 2015)
Youth is the main driving force of development. They should be given the opportunity to voice their opinions and engaged in policy making decisions. As one of the stakeholders, they need to be involved in governance at some levels of the nation’s administration, not only to meet the needs of development in accordance with their wishes but also to prepare them as future leaders of the country. Therefore, this study was conducted to determine the extent of the opportunity to engage youth in decision-making processes at the grassroots level of the Village Development and Security Committee (JKKK) and also the awareness of JKKK members on youth’s involvement in decision-making. Data was gathered by distributing 752 questionnaires to JKKK in Peninsular Malaysia. Descriptive statistics were used to report on the findings. The findings show a moderate involvement of youth in JKKK and high levels of awareness among the respondents regarding the need for youth involvement in decision-making.